Clinical Legal Education at the Faculty of Syariah and Law, Universiti Sains Islam Malaysia - Dina Imam Supaat (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical Legal Education (CLE) is based on the idea that law practice requires thinking and doing. It is founded on the notion of learning by doing in which law students gain lawyering skills by performing lawyering tasks and responsibilities. This method gives students the opportunity to work on actual and simulated cases and solve legal problems systematically. This paper discusses the implementation and application of CLE at the Faculty of Syariah And Law, Universiti Sains Islam Malaysia with emphasis on Problem-based learning, specifically relating to its process, model of PBL activities, targeted skills, student assessment and student feedback. Discussion also covers benefit and challenges of applying CLE and PBL at the faculty. It discusses the experience of the instructor in applying PBL in two courses. This paper comes up with suggestion on the application and implementation of the method in a law school so that law students can master practical legal skills in order to be more employable.